The 30 day fat burner diet - Holford, Patrick (Piatkus, 1999)
Are you always on a diet? Do you eat fewer calories than ever? Do you eat less fat than before? But do you still seem to pile on the pounds? If you are overweight the chances are your body is programmed to turn food into fat instead of energy. Today's diet and stressful, sedentary lifestyles stop you burning away those extra inches. Patrick Holford, Britain's leading nutrition expert, has created a revolutionary way to reverse this process. Discover how to re-program your body to burn off the pounds. No more calorie counting, no more low-fat dieting, no more food combining. Just follow The 30-Day Fatburner Diet to get slim without suffering and control your weight forever! Here, finally, is a diet that really works.